KAJIAN PENINGKATAN KEANDALAN MESIN BOILER MENGGUNAKAN METODE RELIABILITY CENTERED MAINTENANCE PADA INDUSTRI MANUFACTURE SHOCK ABSORBER DI CIKARANG - Agustinus Dwi Susanto (Universitas Mercu Buana, 2017)
This study to analyze critical failure that affects the reliability of the boiler as well as the method used to identify the boiler engine failure. And determining the proper maintenance activity to prevent a critical failure that affects the reliability of this boiler. This research using RCM method for analyzing the condition of the machine boiler. The results showed that the critical Failur the boiler is based on the analysis of RCM is the first component of the feed water pump which has the lowest value of reliabiliy is 0:52 and the highest RPN value 180 that are at risk of failure. The second is the safety valve and the boiler tube failure Safety valve including hiden failure because normally the operator does not know. Failur critical improvement efforts for the boiler is in the form of substitute care policy with prevention to increase the value reliabilitynya as well as activities such as preventive task that is scheduled on-condition task and dischard scheduled task in accordance with thesStandards maintrnance machine that researchers propose.